Attenuation of Severe Generalized Junctional Epidermolysis Bullosa by Systemic Treatment with Gentamicin - Hammersen, Johanna; Neuner, Andrea; Wild, Florian; Schneider, Holm (Dermatology, 2019)
Severe generalized junctional epidermolysis bullosa (JEB), a lethal genodermatosis, is mainly caused by premature termination codons (PTCs) in one of the three genes encoding the anchoring protein laminin-332. Only symptomatic treatment has been established; overcoming PTCs by aminoglycosides may represent an interesting alternative. This retrospective study aimed at assessing for the first time the clinical effects of systemic gentamicin application in infants with severe generalized JEB. Five patients, homozygous or compound-heterozygous for PTCs in the gene LAMB3, were treated with gentamicin which was administered intravenously or by intramuscular injection at doses of 7.5 mg/kg/d for three weeks. Skin biopsies were investigated by immunofluorescence analyses. Clinical effects of the medication were recorded with a parent questionnaire and by assessing weight-for-age charts. Gentamicin application was well tolerated, long hospitalization was not required. Low levels of laminin-332 could be detected in a skin sample obtained after treatment. Gentamicin had a positive impact on skin fragility and daily life in four patients but did not influence weight gain and failed to reverse the lethal course of the disease. Gentamicin injections should be considered regularly in cases of severe generalized JEB caused by PTCs as they may attenuate JEB symptoms without impeding quality of life.
CRIS-Team Scopus Importer:2019-06-18